1999
DOI: 10.1039/a903397a
|View full text |Cite
|
Sign up to set email alerts
|

EPR, ENDOR, TRIPLE resonance spectroscopy and MO studies on radical anion, neutral radical and radical cation of vitamin K3 in a selection of solvents

Abstract: All three radical species (radical anion, neutral radical and radical cation) from 2-methyl-1,4-naphthoquinone (vitamin were prepared in liquid solutions and measured by EPR and ENDOR/TRIPLE resonance K 3 ) spectroscopy. The methyl group protons showed the largest variation of isotropic hyperÐne coupling, from 8.3 MHz (anion) to 19.1 MHz (neutral) to 9.3 MHz (cation). Isotropic hyperÐne couplings of a proton in the quinoid ring and the methyl group protons in di †erent solutions were shown to be dependent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The spectrum shown in Figure a that was obtained at low modulation amplitude and low water content is similar to what has previously been observed and assigned to the VK 1 radical anion in organic solvents. The total widths of the EPR spectra obtained in low- and high-water-content solutions were the same, although the shapes of the spectra were different, indicating slightly different hyperfine coupling constants. It is known that semiquinone anion radicals undergo hydrogen bonding in pure water (or in alcohols), with the interactions having been detected by Q-band pulse 2 H electron–nuclear double resonance experiments .…”
Section: Resultssupporting
confidence: 80%
“…The spectrum shown in Figure a that was obtained at low modulation amplitude and low water content is similar to what has previously been observed and assigned to the VK 1 radical anion in organic solvents. The total widths of the EPR spectra obtained in low- and high-water-content solutions were the same, although the shapes of the spectra were different, indicating slightly different hyperfine coupling constants. It is known that semiquinone anion radicals undergo hydrogen bonding in pure water (or in alcohols), with the interactions having been detected by Q-band pulse 2 H electron–nuclear double resonance experiments .…”
Section: Resultssupporting
confidence: 80%
“…An analogous effect has been observed for nitroxides and quinones: in nonpolar environments the hfc's were reduced with respect to those measured in polar and/or protic solvents. [55][56][57] Aqueous and relatively nonpolar environments have very different dielectric constants, which strongly affect electrontransfer rates, due to their effect on the reorganization energy. In model photolyase systems, Heelis and co-workers showed that the quantum yield of splitting cis,syn-1,3-dimethyluracil dimers is solvent dependent, due to changes in the relative rates for forward and backward electron transfer.…”
Section: Protein Binding Of Fadhmentioning
confidence: 99%
“…Altered hfcs are frequently observed in spin label EPR when one and the same spin probe is exposed to protein regions or solvents of different polarity (Kawamura et al, 1967;Joela and Lehtovuori, 1999;Steinhoff et al, 2000). Whereas such effects are well documented for nitroxide spin labels, the effect of a modified dielectric environment on flavin proton hfcs has not yet been quantified.…”
Section: Model Calculationsmentioning
confidence: 99%